Suicidal Thoughts and Behaviors Among Swedish Suicide-Bereaved Women: Increased Risk Associated With the Loss of a Child, Feelings of Guilt and Shame, and Perceived Avoidance From Family Members - Westerlund, Michael; Hökby, Sebastian; Hadlaczky, Gergö (Frontiers in Psychology, 2020)
Previous studies have shown that suicide bereaved individuals may suffer increased risk for suicidal thoughts and behaviors (STBs) due to traumatic grief. In this paper we present the self-reported rate of STB among Swedish suicide-bereaved women (N = 293). Data was collected in a cross-sectional anonymous survey on the homepages of Sweden’s leading suicide survivor organization, SPES. We used logistic regression to evaluate risks (of any STB event) related to losing a child compared to other relatives, and the experience of social avoidance from family members, as well as feelings of shame and guilt. The self-reported rate of suicidal thoughts, plans and behaviors was 60, 24, and 5 percent respectively, considerably higher than in the general population. Results showed that all of the investigated variables were independent risk factors for STB (ORs ranged between 1.29 and 2.69). Women who had both lost a child and experienced family avoidance reported the highest STB rate (87.7%), and we found an interaction effect between these two risk factors (OR = 3.45; 95% CI = 1.05 – 11.32) that was related to self-reported shame. It is concluded that perceived responsibility for someone else’s suicide, and the social avoidance associated with it, may play an important role for suicide survivors, and should be targeted by postvention activities.